2022
DOI: 10.3390/ijerph19148259
|View full text |Cite
|
Sign up to set email alerts
|

Chinese University Students’ Perspectives on Help-Seeking and Mental Health Counseling

Abstract: Psychological distress and mental illness have become increasingly pervasive among Chinese university students. However, many university students who need mental health treatment or psychological support do not actively seek help from professional counselors or service providers, which could lead to poor mental health outcomes. To promote help-seeking, we undertook a qualitative study to understand Chinese university students’ perspectives on help-seeking and mental health counseling. We conducted 13 focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…As mentioned in the inclusion and exclusion criteria, articles addressing exclusively mental health among university students were excluded due to the enormous number of papers involved and the lack of focus on counseling, the main topic of this systematic review. Consequently, the retained articles included measures of mental health and psychological symptoms but mainly focused on attitudes and concerns toward counseling, counselors, help provider sources, and help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ], expected activities and perceived needs [ 38 ], barriers and demographic predictors to receive professional mental health care [ 39 ]. Demographic characteristics of students and counselors such as gender or ethnicity, as well as acculturation, confidence and openness to mental health and counseling, and family history of mental illness constituted the principal barriers to help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the inclusion and exclusion criteria, articles addressing exclusively mental health among university students were excluded due to the enormous number of papers involved and the lack of focus on counseling, the main topic of this systematic review. Consequently, the retained articles included measures of mental health and psychological symptoms but mainly focused on attitudes and concerns toward counseling, counselors, help provider sources, and help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ], expected activities and perceived needs [ 38 ], barriers and demographic predictors to receive professional mental health care [ 39 ]. Demographic characteristics of students and counselors such as gender or ethnicity, as well as acculturation, confidence and openness to mental health and counseling, and family history of mental illness constituted the principal barriers to help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the retained articles included measures of mental health and psychological symptoms but mainly focused on attitudes and concerns toward counseling, counselors, help provider sources, and help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ], expected activities and perceived needs [ 38 ], barriers and demographic predictors to receive professional mental health care [ 39 ]. Demographic characteristics of students and counselors such as gender or ethnicity, as well as acculturation, confidence and openness to mental health and counseling, and family history of mental illness constituted the principal barriers to help-seeking behaviors [ 33 , 34 , 35 , 36 , 37 ]. A study including 1135 undergraduate university students from Ethiopia [ 39 ] found that the top five barriers to receiving professional mental health care among students were (a) thinking the problem would get better by itself, (b) being unsure where to go to get professional help, (c) wanting to solve the problem on their own, (d) denying a mental health problem, and (e) preferring to get alternative forms of mental care.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason was misconceptions of counseling and stigma of mental illness [71]. When being asked why haven't try school counseling, a student responded that he believed counseling "was only for people who experienced extreme traumatic event like car crush or relatives passing away", while another student directly stated "because I don't have mental illness".…”
Section: E School-based Counseling Servicesmentioning
confidence: 99%
“…The authors delineate three core components: stereotype, prejudice and discrimination and show how these experiences can lead to people shut themselves off and “ not pursu[e] life opportunities for themselves ” (p. 16). Indeed, internationally, stigma and discrimination have consistently been recognised as significant barriers to help‐seeking (Byrow et al, 2019; Martinez et al, 2020; Ning et al, 2022; Salaheddin & Mason, 2016). In an attempt to address these identified barriers, a series of government‐ and nongovernment‐funded anti‐stigma initiatives have been developed and rolled out in multiple countries, including Australia and the UK (Beyondblue, 2015; Henderson & Thornicroft, 2009; SANE, 2022).…”
Section: Introductionmentioning
confidence: 99%